A bioceramic with multi-level pore structure and its preparation method and application

By using calcium carbonate and calcium hydrogen phosphate to form β-tricalcium phosphate, combined with porous sponge template technology, the problem of insufficient degradation performance of β-tricalcium phosphate bioceramics was solved, and a multi-stage pore structure ceramic was prepared with excellent mechanical properties and biocompatible, suitable for bone defect repair and complete degradation in the body.

CN116986920BActive Publication Date: 2025-01-17WUHAN YINGLING MEDICAL BIOTECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310870719.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-14
Publication Date
2025-01-17
Estimated Expiration
2043-07-14

AI Technical Summary

Technical Problem

The existing β-tricalcium phosphate bioceramics are insufficient in vivo degradation and osteogenesis, and high-temperature calcination during processing and preparation reduces its biological activity, lacks good macroscopic communication hole structure and microscopic communication holes, affecting bone conductivity and degradation performance.

Method used

Calcium carbonate and calcium biphosphate are used as raw materials to form β-tricalcium phosphate through high-temperature reaction, and porous sponge template combined with freeze-drying and drying treatment to form bioceramics with multi-stage pore structures, avoiding the defects of micronization treatment and enhancing the The hydrophilicity and degradation properties of the material, and a macroporous structure close to the cancellous bone structure is designed.

Benefits of technology

The obtained multi-stage pore structure bioceramics have excellent mechanical properties and biocompatibility, can quickly stimulate and guide bone tissue regeneration, with high porosity and connectivity, and are suitable for bone defect repair and complete degradation in the body, satisfying the Clinical needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116986920B_ABST
    Figure CN116986920B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a bioceramic with a multi-level pore structure, comprising the following steps: first, calcium carbonate and calcium hydrogen phosphate are placed in a polyvinyl alcohol solution in a certain proportion, and a slurry is obtained by emulsification treatment; secondly, the slurry is fully adsorbed by a porous sponge template, freeze-dried, and then placed in water for immersion, and then dried to obtain a green embryo; finally, the green embryo is calcined to obtain a bioceramic with a multi-level pore structure. The main component of the bioceramic prepared by the present invention is β-tricalcium phosphate, which has a multi-level pore structure, and there are 1 to 10 μm interconnected micropores on the trabeculae, which is conducive to the degradation of the material, the porosity is greater than 65%, and the pore connectivity is greater than 90%. The bioceramic is used as an artificial bone material for bone defect repair, has excellent biocompatibility and pore structure, can quickly stimulate and guide tissue regeneration, can be completely degraded after implantation in the body, meets clinical needs, and has broad prospects for promotion and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomedical materials, and in particular relates to a bioceramic with a multi-level pore structure and a preparation method thereof, and also relates to an application of the bioceramic with a multi-level pore structure in bone defect repair. Background Art

[0002] Artificial bone materials are being widely studied due to their wide range of sources and diversity. Among them, β-tricalcium phosphate (β-TCP) porous bioceramics are gradually being favored by clinicians due to their suitable degradation rate. At the same time, they also perform very well in biocompatibility and osteoconduction. This is mainly due to the fact that β-TCP is similar to bone tissue composition, and the various ions produced during the degradation process can follow the human body's metabolism and be absorbed and utilized by the human body for the second time, achieving a dynamic balance between the degradation of non-living β-TCP and the growth of living bones.

[0003] Dense β-TCP bioceramics are not conducive to the degradation of materials in the body, and the high calcination temperature during its processing and preparation will also reduce its biological activity. For β-TCP bioceramics, without a good macroscopic interconnected pore structure, good osteoconductivity cannot be achieved; and without good microscopic interconnected pores, the degradation performance and hydrophilicity of the material will be reduced, greatly reducing its osteogenic ability.

[0004] Based on this, developing a bioceramic material with a multi-level pore structure to address the shortcomings of current bioceramic products in terms of insufficient degradation and osteogenic properties has important research and application significance, and is also a technical problem that urgently needs to be solved in current clinical research. Summary of the invention

[0005] One of the purposes of the present invention is to provide a method for preparing a bioceramic with a multi-level porous structure that is conducive to material degradation and has excellent osteogenic performance.

[0006] A second object of the present invention is to provide a bioceramic with a multi-level porous structure that is conducive to material degradation and has excellent osteogenic performance.

[0007] A third object of the present invention is to provide a bioceramic with a multi-level pore structure for use as an artificial bone material in bone defect repair.

[0008] The technical solution adopted by the present invention to achieve one of the purposes is: to provide a method for preparing a bioceramic with a multi-level pore structure, comprising the following steps:

[0009] S1. Adding calcium carbonate and calcium hydrogen phosphate in a certain proportion into a binder solution, and emulsifying the solution to obtain a slurry;

[0010] S2, completely immersing the porous sponge template in the slurry to allow it to be fully adsorbed, freeze-drying the adsorbed porous sponge template, then soaking it in water, and then drying it to obtain a green embryo;

[0011] S3, placing the green body at a certain temperature for calcination to obtain a bioceramic with a multi-level porous structure.

[0012] The general idea of ​​the preparation method of a bioceramic with a multi-level pore structure provided by the present invention is as follows:

[0013] First, the present invention does not directly use conventional β-tricalcium phosphate as a raw material to prepare bioceramics, but uses calcium carbonate and calcium hydrogen phosphate as raw materials, and then forms β-tricalcium phosphate through a high-temperature reaction between the two, and then further sintering to form bioceramics. The above preparation process avoids the problem of conventional micronization of β-tricalcium phosphate powder, which leads to the destruction of the connection characteristics between powders. Compared with conventional β-tricalcium phosphate, the bioceramics obtained by further preparing the homemade β-tricalcium phosphate not only have better mechanical properties, but also a simpler preparation process; at the same time, with the help of a large amount of gas generated by the mutual reaction of calcium carbonate and calcium hydrogen phosphate during the high temperature process, a connected microporous structure is formed, which enhances the hydrophilicity and degradation performance of the bioceramic material.

[0014] Secondly, the present invention adopts a porous sponge template combined with freeze drying and drying treatment to achieve the design of the macroscopic pore structure of bioceramics. Compared with traditional compression molding, the preparation method provided by the present invention is simpler, has better pore connectivity, and is structurally closer to the cancellous bone structure, which is more conducive to guiding the regeneration of bone tissue.

[0015] Finally, the green embryo formed by the sponge template method was subjected to high-temperature calcination to remove organic matter, thereby obtaining a bioceramic whose main component is β-tricalcium phosphate and has a multi-level pore structure.

[0016] Furthermore, in step S1, the molar ratio of calcium carbonate to calcium hydrogen phosphate is (3-4):6, and the composition is controllable. By simply changing the raw materials and adjusting the proportions, the composition can be diversified to meet different needs. Preferably, the molar ratio of calcium carbonate to calcium hydrogen phosphate is 1:2, and the β-tricalcium phosphate of the bioceramic prepared under this condition has a higher purity. In addition, for bone grafting in special parts, the bone grafting material may be required to have better mechanical strength and a slower degradation rate. In the present invention, by increasing the amount of calcium carbonate, the main component of the prepared bioceramic contains a certain proportion of hydroxyapatite to meet the application requirements.

[0017] Furthermore, the binder solution is selected from a polyvinyl alcohol solution. The polyvinyl alcohol solution is used as a binder to fix the raw materials on the porous sponge template. On the one hand, it helps the porous sponge template to fully adsorb the reaction raw materials (calcium carbonate and calcium hydrogen phosphate); on the other hand, it can form a better interconnected pore structure in subsequent processing. Preferably, in the polyvinyl alcohol solution, the mass ratio of polyvinyl alcohol to water is (2-6):100; the mass ratio of the total mass of calcium carbonate and calcium hydrogen phosphate to the polyvinyl alcohol solution is 60:(70-80).

[0018] Preferably, the method for preparing the polyvinyl alcohol solution comprises: adding 2-6 wt % polyvinyl alcohol into water, and continuously stirring at 90-100° C. until a uniform solution is obtained.

[0019] Furthermore, in step S1, the rotation speed of the emulsification treatment is 4000-10000 rpm / min, and the time of the emulsification treatment is 10-30 min. Preferably, the rotation speed of the emulsification treatment is 5000-6000 rpm / min.

[0020] Preferably, in step S2, the sponge quality of the porous sponge template is 40-50 ppi.

[0021] Preferably, in step S2, the porous sponge template is selected from polyurethane sponge.

[0022] Furthermore, in step S2 of the present invention, the porous sponge template is first completely immersed in the slurry. In the excess slurry, the porous sponge template fully absorbs the slurry so that the pore structure of the porous sponge template is fully filled with the slurry; then the porous sponge template that absorbs the slurry is freeze-dried and then immersed in water to soften the sponge template; finally, it is dried at a certain temperature, and the pores of the porous sponge template are shrunk, thereby achieving a better pore-making effect.

[0023] Preferably, the pre-freezing temperature of freeze drying is -40 to -50°C, the pre-freezing time is 2 to 3 hours, the final drying temperature is -5 to 5°C, and the drying time is 48 to 72 hours. In the present invention, the porous sponge template after freeze drying is placed in water for soaking, and then dried. Preferably, the temperature of the drying treatment is 50 to 100°C, and the drying time is 20 to 30 hours. More preferably, the temperature of the drying treatment is 60 to 80°C.

[0024] Furthermore, in step S3, the temperature of the calcination treatment is 1100-1300°C, and the calcination treatment time is 2-3h. Preferably, the green embryo is first heated from room temperature to 500-600°C, with a heating rate of 1-5°C / min, and kept warm for 2h; then heated to 900-1000°C, with a heating rate of 5-10°C / min, and kept warm for 2h; finally heated to 1100-1300°C, with a heating rate of 5-10°C / min, and kept warm for 2h. Preferably, the temperature is finally raised to 1150-1200°C. In the present invention, a step-by-step heating method is used in conjunction with a heat preservation operation to promote the full decomposition of calcium carbonate, release CO2, and finally form a microporous structure of suitable size and interconnected.

[0025] The technical solution adopted by the present invention to achieve the second purpose is: to provide a bioceramic with a multi-level porous structure prepared by the preparation method described in one of the purposes of the present invention.

[0026] The main component of the bioceramic is β-tricalcium phosphate or a mixture of β-tricalcium phosphate and hydroxyapatite, the porosity is greater than 65%, the pore connectivity is greater than 90%, and the pores include macropores and micropores; the pore diameter of the macropores is 100-500 μm; the pore diameter of the micropores is 1-10 μm.

[0027] The bioceramics prepared by the invention have interconnected micropores of 1 to 10 μm on the trabeculae, which are conducive to the degradation of the material, the porosity is greater than 65%, the pore interconnectivity is greater than 90%, and it is conducive to the growth and conduction of bone tissue.

[0028] The technical solution adopted by the present invention to achieve the third purpose is: to provide an application of a bioceramic with a multi-level pore structure, wherein the bioceramic is prepared by the preparation method according to one of the purposes of the present invention; the bioceramic is used as an artificial bone material for bone defect repair. The bioceramic has excellent biocompatibility and pore structure, can quickly stimulate and guide tissue regeneration, and can be completely degraded after implantation in the body, meeting clinical needs.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The present invention provides a method for preparing a bioceramic with a multi-level porous structure, which uses calcium carbonate and calcium hydrogen phosphate as raw materials, forms β-tricalcium phosphate through high temperature, and then further sinters to form ceramics, avoiding the conventional micronization treatment of β-tricalcium phosphate powder, and the obtained bioceramics have better mechanical properties. The present invention uses a sponge template method combined with freeze drying and room temperature drying to design the macroscopic pore structure of bioceramics. Compared with traditional compression molding, it is simpler and has better pore connectivity. The structure is closer to the cancellous bone structure, which is more conducive to guiding the regeneration of bone tissue. At the same time, with the help of a large amount of gas generated by high-temperature heat treatment, a connected microporous structure is formed in the bioceramic, enhancing the hydrophilicity and degradation performance of the material.

[0031] (2) The bioceramic with a multi-level porous structure prepared by the present invention has β-tricalcium phosphate as its main component. There are interconnected micropores of 1 to 10 μm on the trabeculae, which are conducive to the degradation of the material. The porosity is greater than 65%, and the pore connectivity is greater than 90%, which is conducive to the ingrowth and conduction of bone tissue. The bioceramic is used as an artificial bone material for bone defect repair. It has excellent biocompatibility and pore structure, can quickly stimulate and guide tissue regeneration, and can be completely degraded after implantation in the body, meeting clinical needs and having broad prospects for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a SEM image of the bioceramic prepared in Example 1 of the present invention;

[0033] Figure 2 is the pore distribution curve of the bioceramic prepared in Example 1 of the present invention;

[0034] Figure 3 The XRD curve of the bioceramic prepared in Example 1 of the present invention;

[0035] Figure 4 IR curve of the bioceramic prepared in Example 1 of the present invention;

[0036] Figure 5 This is a HE staining picture of the bioceramic prepared in Example 1 of the present invention after 6 weeks of rat skull implantation experiment;

[0037] Figure 6 This is a HE staining picture of the bioceramic rabbit femoral condyle obtained in Example 1 of the present invention after 8 weeks of implantation test;

[0038] Figure 7 This is an appearance diagram of the bioceramic prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0039] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0041] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited thereto.

[0042] Example 1

[0043] A multi-level porous structure bioceramic, the preparation method of which comprises the following steps:

[0044] Step 1: Add 5 wt % polyvinyl alcohol to water, continue stirring at 95 ° C until a uniform solution is obtained, add calcium carbonate and calcium hydrogen phosphate, the molar ratio of calcium carbonate to calcium hydrogen phosphate is 1:2, and the ratio of the total mass of calcium carbonate and calcium hydrogen phosphate to the mass of the polyvinyl alcohol solution is 60:80, and emulsify for 20 minutes at 6000 r / min by an emulsifier to obtain a slurry.

[0045] Step 2: After the slurry is cooled, 40ppi polyurethane sponge is immersed in the slurry to allow it to be completely adsorbed, then frozen at -45°C for 2h, freeze-dried at -5°C for 72h, soaked in water, and then dried at 80°C for 20h to obtain a green embryo.

[0046] Step 3: Place the embryo in a muffle furnace, first heat it from room temperature to 550°C, at a heating rate of 2°C / min, and keep it warm for 2 hours; then heat it to 900°C, at a heating rate of 8°C / min, and keep it warm for 2 hours; finally heat it to 1200°C, at a heating rate of 5°C / min, and keep it warm for 2 hours to obtain bioceramics. The bioceramics are packaged and sterilized by irradiation to obtain bioceramics with a multi-level porous structure.

[0047] Example 2

[0048] A multi-level porous structure bioceramic, the preparation method of which comprises the following steps:

[0049] Step 1: Add 3 wt % polyvinyl alcohol to water, continue stirring at 95 ° C until a uniform solution is obtained, add calcium carbonate and calcium hydrogen phosphate, the molar ratio of calcium carbonate to calcium hydrogen phosphate is 1:2, and the ratio of the total mass of calcium carbonate and calcium hydrogen phosphate to the mass of the polyvinyl alcohol solution is 60:70, and emulsify for 20 minutes at 5000 r / min by an emulsifier to obtain a slurry.

[0050] Step 2: After the slurry is cooled, 50ppi polyurethane sponge is immersed in the slurry to allow it to be completely adsorbed, then frozen at -45°C for 2h, freeze-dried at 0°C for 60h, soaked in water, and then dried at 80°C for 20h to obtain a green embryo.

[0051] Step 3: Place the embryo in a muffle furnace, first heat it from room temperature to 550°C at a rate of 2°C / min, and keep it warm for 2 hours; then heat it to 900°C at a rate of 8°C / min, and keep it warm for 2 hours; finally heat it to 1150°C at a rate of 5°C / min, and keep it warm for 3 hours to obtain bioceramics. The bioceramics are packaged and sterilized by irradiation to obtain bioceramics with a multi-level porous structure.

[0052] Example 3

[0053] A multi-level porous structure bioceramic, the preparation method of which comprises the following steps:

[0054] Step 1: Add 4 wt % polyvinyl alcohol to water, continue stirring at 95 ° C until a uniform solution is obtained, add calcium carbonate and calcium hydrogen phosphate, the molar ratio of calcium carbonate to calcium hydrogen phosphate is 1:2, and the ratio of the total mass of calcium carbonate and calcium hydrogen phosphate to the mass of the polyvinyl alcohol solution is 60:75, and emulsify for 20 minutes at 6000 r / min by an emulsifier to obtain a slurry.

[0055] Step 2: After the slurry is cooled, immerse a 40ppi polyurethane sponge into the slurry to allow it to be completely adsorbed, then freeze it at -45°C for 2 hours, freeze-dry it at 5°C for 48 hours, soak it in water, and then dry it at 80°C for 20 hours to obtain a green embryo.

[0056] Step 3: Place the embryo in a muffle furnace, first heat it from room temperature to 550°C, at a heating rate of 2°C / min, and keep it warm for 2 hours; then heat it to 900°C, at a heating rate of 8°C / min, and keep it warm for 2 hours; finally heat it to 1150°C, at a heating rate of 5°C / min, and keep it warm for 2 hours to obtain bioceramics. The bioceramics are packaged and sterilized by irradiation to obtain bioceramics with a multi-level porous structure.

[0057] Example 4

[0058] A multi-level porous structure bioceramic, the preparation method of which comprises the following steps:

[0059] Step 1: Add 4 wt % polyvinyl alcohol to water, continue stirring at 95 ° C until a uniform solution is obtained, add calcium carbonate and calcium hydrogen phosphate, the molar ratio of calcium carbonate to calcium hydrogen phosphate is 1:2, and the ratio of the total mass of calcium carbonate and calcium hydrogen phosphate to the mass of the polyvinyl alcohol solution is 60:80, and emulsify for 20 minutes at 6000 r / min by an emulsifier to obtain a slurry.

[0060] Step 2: After the slurry is cooled, 50ppi polyurethane sponge is immersed in the slurry to allow it to be completely adsorbed, then frozen at -45°C for 2h, freeze-dried at 0°C for 60h, soaked in water, and then dried at 60°C for 25h to obtain a green embryo.

[0061] Step 3: Place the embryo in a muffle furnace, first heat it from room temperature to 550°C, at a heating rate of 2°C / min, and keep it warm for 2 hours; then heat it to 900°C, at a heating rate of 8°C / min, and keep it warm for 2 hours; finally heat it to 1200°C, at a heating rate of 5°C / min, and keep it warm for 2 hours to obtain bioceramics. The bioceramics are packaged and sterilized by irradiation to obtain bioceramics with a multi-level porous structure.

[0062] Example 5

[0063] A multi-level porous structure bioceramic, the preparation method of which comprises the following steps:

[0064] Step 1: Add 5 wt % polyvinyl alcohol to water, continue stirring at 95 ° C until a uniform solution is obtained, add calcium carbonate and calcium hydrogen phosphate, the molar ratio of calcium carbonate to calcium hydrogen phosphate is 3.2:6, and the ratio of the total mass of calcium carbonate and calcium hydrogen phosphate to the mass of the polyvinyl alcohol solution is 60:80, and emulsify for 20 minutes at 6000 r / min by an emulsifier to obtain a slurry.

[0065] Step 2: After the slurry is cooled, 40ppi polyurethane sponge is immersed in the slurry to allow it to be completely adsorbed, then frozen at -45°C for 2h, freeze-dried at -5°C for 72h, soaked in water, and then dried at 80°C for 20h to obtain a green embryo.

[0066] Step 3: Place the embryo in a muffle furnace, first heat it from room temperature to 550°C, at a heating rate of 2°C / min, and keep it warm for 2 hours; then heat it to 900°C, at a heating rate of 8°C / min, and keep it warm for 2 hours; finally heat it to 1200°C, at a heating rate of 5°C / min, and keep it warm for 2 hours to obtain bioceramics. The bioceramics are packaged and sterilized by irradiation to obtain bioceramics with a multi-level porous structure.

[0067] In this embodiment, a multi-level porous structure bioceramic is prepared by increasing the molar ratio of calcium carbonate in the raw material. Its main component is a mixture of β-tricalcium phosphate and hydroxyapatite. Hydroxyapatite can further improve the mechanical properties of the bioceramic and slow down the degradation rate, thereby meeting the bone grafting requirements under some special clinical conditions.

[0068] Performance Testing

[0069] The multi-level porous structure bioceramics prepared in Examples 1-5 were subjected to relevant performance tests, including mechanical strength, open porosity and pore connectivity. The results are shown in Table 1 below.

[0070] Table 1

[0071]

[0072] As can be seen from the above table,

[0073] The bioceramics prepared in Examples 1-4 of the present invention have a mechanical strength of 2.86 to 4.05 MPa, an open porosity of 66.81% to 70.47%, and a pore connectivity of 94% to 96%. The bioceramics prepared in Example 5 have higher mechanical properties due to the presence of hydroxyapatite in its components, and have a mechanical strength of 8.46 MPa.

[0074] Figure 1 This is a SEM image of the bioceramic prepared in Example 1 of the present invention, in which a connected macroscopic pore structure with a pore diameter of about 200 microns and a microscopic pore structure with a pore diameter of 1 to 10 microns can be seen. Figure 2 This is the pore distribution curve of the bioceramic prepared in Example 1 of the present invention. It can be seen from the figure that the pores are mainly distributed between 100-500 microns and 1-10 microns, which is a multi-level pore structure, which is consistent with the SEM result.

[0075] Figure 3 The XRD curve of the bioceramic prepared in Example 1 of the present invention shows the characteristic peak of β-tricalcium phosphate and no other impurity peaks, indicating that the content of β-tricalcium phosphate in the bioceramic is more than 95%. Figure 4 This is the IR curve of the bioceramic prepared in Example 1 of the present invention. Only the infrared characteristic peak of phosphate can be seen, and there are no other impurity peaks.

[0076] Figure 5 This is a HE staining picture of the bioceramic prepared in Example 1 of the present invention after 6 weeks of rat skull implantation test. From the section results, it can be seen that the tissue has completely grown into the ceramic, and a large number of red blood cells and mesenchymal stem cells can be seen. The blood vessels are conducive to the delivery of nutrients and the transformation of mesenchymal stem cells into osteoblasts and osteocytes. At the same time, a small amount of new bone tissue can be seen inside, indicating that the pore structure of the bioceramic is conducive to the growth of cells and guiding the regeneration of bone tissue.

[0077] Figure 6 This is a HE staining picture of the bioceramic rabbit femoral condyle implanted 8 weeks after the experiment. Figure 6 It can be seen that a large amount of new bone tissue grows between the ceramic particles, some materials are initially degraded, and a large number of red blood cells and mesenchymal stem cells are conducive to the further growth of bone tissue.

[0078] Figure 7 This is the appearance of the bioceramic prepared in Example 1 of the present invention. It can be seen that under the light, the light can penetrate the ceramic and an obvious pore structure can be seen, indicating that the bioceramic has a connected pore structure.

[0079] In summary, the present invention provides a method for preparing a bioceramic with a multi-level porous structure. The prepared bioceramic is used as an artificial bone material for bone defect and repair. It has excellent biocompatibility and pore structure, is conducive to the ingrowth and conduction of bone tissue, can quickly stimulate and guide tissue regeneration, can be completely degraded after implantation in the body, meets clinical needs, and has broad prospects for promotion and clinical application.

[0080] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the contents of the specification of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a bioceramic with a multi-level pore structure, characterized in that: The following steps are involved: S1. Calcium carbonate and calcium hydrogen phosphate are placed in a polyvinyl alcohol solution at a molar ratio of (3-4):6, and subjected to emulsification treatment to obtain a slurry; in the polyvinyl alcohol solution, the mass ratio of polyvinyl alcohol to water is (2-6):100; the mass ratio of the total mass of calcium carbonate and calcium hydrogen phosphate to the polyvinyl alcohol solution is 60:(70-80); S2, completely immersing the porous sponge template in the slurry to allow it to be fully adsorbed, freeze-drying the adsorbed porous sponge template, then soaking it in water, and then drying it to obtain a green embryo; the porous sponge template is selected from a polyurethane sponge with a sponge quality of 40-50ppi; S3, heating the green embryo from room temperature to 500-600° C. at a heating rate of 1-5° C. / min, and keeping the temperature for 2 hours; Then the temperature is raised to 900~1000℃, the heating rate is 5~10℃ / min, and the temperature is kept for 2h; Finally, the temperature was raised to 1100-1300°C at a rate of 5-10°C / min and kept at this temperature for 2 hours to obtain a bioceramic with a multi-level porous structure.

2. The preparation method according to claim 1, characterized in that: In step S1, the rotation speed of the emulsification treatment is 4000-10000 rpm / min, and the time of the emulsification treatment is 10-30 min.

3. The preparation method according to claim 1, characterized in that: In step S2, the pre-freezing temperature of freeze drying is -40~-50°C, and the pre-freezing time is 2~3h; the final drying temperature of freeze drying is -5~5°C, and the final drying time is 48~72h.

4. The preparation method according to claim 1, characterized in that: In step S2, the drying temperature is 50-100°C, and the drying time is 20-30 hours.

5. A bioceramic with a multi-level pore structure, characterized in that: The bioceramic is prepared by the preparation method according to any one of claims 1 to 4, wherein the main component of the bioceramic is β-tricalcium phosphate or a mixture of β-tricalcium phosphate and hydroxyapatite, and its porosity is greater than 65%, and the pore connectivity is greater than 90%; the pores include macropores and micropores; the pore size of the macropores is 100-500 μm; and the pore size of the micropores is 1-10 μm.

6. Application of a bioceramic with a multi-level pore structure, wherein the bioceramic is prepared by the preparation method according to any one of claims 1 to 4; characterized in that: The bioceramic is used as an artificial bone material for repairing bone defects.

Citation Information

Patent Citations

  • Bio-ceramic stent and applications thereof

    CN110227178A

  • Method for preparing CaO-P2O5-MgO glass reinforced porous beta-tricalcium phosphate bioceramics

    CN1830907A